Evaluation of "The state of OSH in the European Union" : pilot study (Bilbao, 2001)
"The European Agency information project “The State of Occupational Safety and Health in the European Union - Pilot Study” is a first step to the development of a system for monitoring the safety and health in the European Union. It aims at providing decision-makers at Member State and European level with an overview of the current safety and health situation in the European Union and in this way supporting the identification of common challenges and priority areas for preventive actions. The project report identifies for physical exposures, postures and movement exposures, handling chemicals, psycho-social working conditions and occupational safety and health outcome for example sectors/occupations most identified to be at risk. Further, the Focal Points and their national networks provided information on trends and needs for development of additional preventive actions related to these indicators. Implications of the “changes in working life” on occupational safety and health are also touched in this report. "